Anaerobic Co-digestion of Olive-mill Solid Waste with Cattle Manure and Cattle Slurry: Analysis of Bio-methane Potential. (December 2015) - Carlini, Maurizio; Castellucci, Sonia; Moneti, Marta
Abstract: In the present work, the bio-methane potential from anaerobic digestion of OMSW with inoculum and co-digestion of OMSW with cattle manure (CM) and cattle slurry (CS) has been analysed. The OMSW used for the analysis was a pollutant waste came from olive oil processing through three-phase centrifugation systems. A batch stirred tank reactor has been used, under mesophilic conditions (38 °C), in order to study the biogas yield. The whole process has been carried out under wet conditions, and with a Hydraulic Retention Time (HRT) of 55 days. Several tests have been carried out to achieve the best biogas yield.